2007
DOI: 10.1086/513514
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Tidal Interactions and Mergers as the Origin of Galaxy Morphology Evolution in Compact Groups

Abstract: We present the results of a morphological study based on NIR images of 25 galaxies, with different levels of nuclear activity (star formation or AGN), in 8 Compact Groups of Galaxies (CGs). We perform independently two different analysis: a study of the deviations of isophotal levels from pure ellipses and a study of morphological asymmetries. The results yielded by the two analysis are highly consistent. For the first time, it is possible to show that deviations from pure ellipses are produced by inhomogeneou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 63 publications
3
58
0
Order By: Relevance
“…This is confirmed by a number of studies that have shown distorted kinematics and morphologies of compact group galaxies (e.g. Presotto et al 2010;Amram et al 2007;Coziol & Plauchu-Frayn 2007;Amram et al 2003;Plana et al 2003Plana et al , 1998, also by studies of groups containing HI tidal debris (Verdes-Montenegro et al 2001) and newly formed stars forming systems outside the luminous member galaxies (e.g. de Mello et al 2008), as well as studies of diffuse light presumably originated from stripped material from the outskirts of galaxies in compact groups (e.g.…”
Section: Outliers From the Tf Relationmentioning
confidence: 60%
“…This is confirmed by a number of studies that have shown distorted kinematics and morphologies of compact group galaxies (e.g. Presotto et al 2010;Amram et al 2007;Coziol & Plauchu-Frayn 2007;Amram et al 2003;Plana et al 2003Plana et al , 1998, also by studies of groups containing HI tidal debris (Verdes-Montenegro et al 2001) and newly formed stars forming systems outside the luminous member galaxies (e.g. de Mello et al 2008), as well as studies of diffuse light presumably originated from stripped material from the outskirts of galaxies in compact groups (e.g.…”
Section: Outliers From the Tf Relationmentioning
confidence: 60%
“…Subsequent spectroscopy studies have shown that the majority of the HCG have galaxies with concordant redshifts (Hickson et al 1992), which display many signs of interactions in the form of tidal tails, tidal bridges, distorted isophotes, faint shells, and double nuclei (Mendes de Oliveira & Hickson 1994;Hickson 1997;Verdes-Montenegro et al 2001, 2002, 2005Coziol & Plauchu-Frayn 2007;Plauchu-Frayn & Coziol 2010a). Asymmetrical rotation curves have also been detected (Rubin et al 1991;Nishiura et al 2000;Torres-Flores et al 2010) and, contrary to what was assumed in the past, various evidence for present and past mergers has also clearly been established (Caon et al 1994;Coziol & Plauchu-Frayn 2007;Plauchu-Frayn & Coziol 2010b). All these observations are consistent with the initial assumption which, sustains that CG are physically real structures in which galaxies have experienced frequent dynamical interactions during their formation and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, strong mergers in CGs are rare (Mendes de Oliveira & Hickson 1994) and much effort has been made to establish the origin and fate of these systems. Coziol & Plauchu-Frayn (2007) showed that galaxies in compact groups are more likely to merge under dry conditions, after they have lost most of their gas in interactions with galaxies. This hypothesis is corroborated by HI studies: Verdes-Montenegro et al (2001) detected perturbed distributions of neutral hydrogen in CGs.…”
Section: Introductionmentioning
confidence: 99%